2018
DOI: 10.12691/ajmr-6-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical Characterization of a Pink Red-like Pigments Produced by Five New Bacterial Soil Strains Identified as <i>Streptomyces coelicoflavus</i>

Abstract: Five new strains MFB11, MFB20, MFB21, MFB23 and MFB24 of actinomycetes showed an intracellular hydrophobic pink red-like pigment production. These pigments present similar physico-chemical characteristics with anthracycline antibiotics of prodigiosin family. Nevertheless, negative antibacterial assay, Thinlayer chromatography (TLC) and interaction with organic solvents analysis of these pigments revealed their difference from known anthracycline antibiotics. Morphological, biochemical and gene coding 16S RNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The absence of pigment formation in ISP2 broth during submerged fermentation could be explained by the culture composition since most biopigments are secreted under stress conditions [ 56 ]. Similar bacterial magenta pigments have been extracted using different organic solvents [ 57 , 58 ]. A pink/red-like pigment (λ max = 534 nm) produced by Streptomyces coelicoflavus was reported by Assia et al [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of pigment formation in ISP2 broth during submerged fermentation could be explained by the culture composition since most biopigments are secreted under stress conditions [ 56 ]. Similar bacterial magenta pigments have been extracted using different organic solvents [ 57 , 58 ]. A pink/red-like pigment (λ max = 534 nm) produced by Streptomyces coelicoflavus was reported by Assia et al [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar bacterial magenta pigments have been extracted using different organic solvents [ 57 , 58 ]. A pink/red-like pigment (λ max = 534 nm) produced by Streptomyces coelicoflavus was reported by Assia et al [ 57 ]. According to the authors, the spectral characteristics of these pigments are consistent with nonantibiotic hydrophobic anthracyclines with intracellular localization and photosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…They also contain different biological properties like antioxidants, anti-inflammatory, antifungal, and anti-carcinogenic properties which makes them suitable for the food and pharmaceutical industries [ 30 ]. Apart from food and pharmaceuticals, bacterial pigments have application in several fields such as pigment pyocyanin from Pseudomonas aeruginosa as textile dye [ 31 ], phycocyanin from Nostoc linckia for the synthesis of silver nanoparticles [ 32 ], prodigiosin from Serratia marcescens for the synthesis of dye-sensitized solar cells [ 33 ], Violacein from Chromobacterium violaceum as immunostimulator with potential to be applied in immune therapies [ 34 ] and many others as listed in Table 1 [ [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. The applicability of bacterial pigment in various industries displays its potential to compete commercially with the existing synthetic pigments in the market.…”
Section: Introductionmentioning
confidence: 99%
“… Serratia marcescens American type culture collection Prodigiosin Fabric dye [ 35 ] 2. Chryseobacterium artocarpi Orchard soil Flexirubin [ 36 ] 3. Streptomyces coelicoflavus Soil Red pigment Anthracyclines analog [ 37 ] 4.…”
Section: Introductionmentioning
confidence: 99%
“…Among actinomycetes, the genus Streptomyces is considered to be the most prolific producer of secondary metabolites for medical, agricultural and veterinary usage [8,9,10]. Previous reports showed that the Streptomyces genus has the ability to produce a variety of secondary metabolites with various activities, including antimicrobial, anticancer, and antiparasitic [11,12,13].…”
Section: Introductionmentioning
confidence: 99%